Analisis Anggaran Penjualan dan Kas pada Usaha Mikro Yeyes Dapur - Dinda Ratna Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The national economy relies on micro, small, and medium-sized businesses (MSMBs). The implementation of a structured and planned budgeting system is one area where many firms still encounter difficulties with financial management. An essential tool for financial management, budgets help in planning, controlling, and evaluating a company's financial performance, which in turn ensures efficient and effective use of resources. Yeyes Dapur is a micro, small, and medium enterprise (MSME) in the food service industry, and this research will examine its budgeting practices and how they have helped the company achieve financial success. Direct observation of operational activities, interviews with the business owner, and documentation of financial data covering sales, production, raw materials, labor, operational costs, cash budgets, and break-even analysis make up the research method used, which is a descriptive quantitative case study approach. The findings show that the owner of Yeyes Dapur is able to better anticipate operating demands, regulate expenditures, and manage cash flow after implementing a budget. The break-even analysis further reveals that the business is in a profitable condition, as actual sales have exceeded the established break-even point. However, several limitations remain, particularly related to the completeness and level of detail in financial record-keeping.